The Alaska Constitution (Book collections on Project MUSE., 2020)
"The Alaska State Constitution, ratified by the people in 1956, became operative with the proclamation of statehood on January 3, 1959. The constitution was drafted by fifty-five delegates who convened at the University of Alaska to determine the authority vested in the state legislature, executive, judiciary, and other functions of government. This conveniently sized new edition will make the Alaska State Constitution accessible to all"--